2021
DOI: 10.1002/1348-9585.12264
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between personal-sampled air lead and blood lead in low-lead-exposure workers in Japan to apply multiple regression models determining permissible air lead concentration

Abstract: Objectives We investigated the relationship between lead in air (Pb‐A) measured by personal sampling and blood lead (Pb‐B) in workers with relatively low lead exposure to estimate the permissible air concentration of lead corresponding to the biological tolerance value of Pb‐B of 15 µg/dL. Methods We collected air samples at a lead‐acid battery factory in Japan by personal sampling devices attached to 32 workers (19 males and 13 females) and measured Pb‐A by a graphite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…It was shown that there was no significant difference between the mean BLC of two groups. In line with our study, Ono (2021) found no significant difference between BLC in smoker and non-smoker workers in Japan 23 ; moreover, a study already done in Tunisia (2019) on battery manufacturing workers showed that there was no significant difference between the BLC of cigarette-smoker and non-smoker workers. The close association between cigarette smoking habit and BLC in some studies could be attributed to some confounding factors 43 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was shown that there was no significant difference between the mean BLC of two groups. In line with our study, Ono (2021) found no significant difference between BLC in smoker and non-smoker workers in Japan 23 ; moreover, a study already done in Tunisia (2019) on battery manufacturing workers showed that there was no significant difference between the BLC of cigarette-smoker and non-smoker workers. The close association between cigarette smoking habit and BLC in some studies could be attributed to some confounding factors 43 .…”
Section: Discussionsupporting
confidence: 91%
“…Base on the results of this research, the mean BLC of automobile welders and the mean ALC were significantly lower than the permissible limit recommended by ACGIH; moreover, Pearson correlation coefficient demonstrated a positive correlation (r = 0.18) between ALCs and BLCs. A significant correlation between ALC and BLC of the workers being occupationally exposed to lead-containing aerosols, has been reported by Ono (2021) and Pierre (2002) 23,24 .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Worksite parameters and substantive lowering of personal hygiene standards have shown in several studies to be associated with elevated BLLs [13,25,26]. In addition, behaviors involving hand-to-mouth contact such as smoking and eating while at work may lead to additional exposure via ingestion.…”
Section: Discussionmentioning
confidence: 99%